دراسة أشكال حبات النشاء وحبات الطلع عند 10 أنواع من نبات الحلبوب (L. Euphorbia) - حداد, دينا (Latakia University Journal -Biological Sciences Series, 2017)
أوضحت هذه الدراسة وجود أشكال وأحجام مختلفة لحبات النشاء في السائل الحليبي لـ 10 أنواع من جنس الحلبوب Euphorbia وهي :E.prostrata , E. serpens , E.pilulifera , E.geniculata , E. thamnoidesE. helioscopia , E. aleppica , E. peplus , E. terracina , E. paralias، وتباينت بين عصوي، مغزلي ، شبيه العظم ، عظمي، دمبل ، وعظمي متفرع ، وأشكال وسطية مع تسنن وملحقات . كما أوضحت دراسة حبات الطلع لهذه الأنواع أنها كروية ،أو بيضوية الشكل ثلاثية خطوط وثقوب الانتاش، وهي من النمط الإيفوربيا – المشعرة . تميزت تزينات السطح بأنها شبكية خشنة عند النوع (E.geniculata) فقط ، أما بقية الانواع فكانت شبكية ناعمة، وبالنسبة لحجم حبة الطلع اختلف أيضاً بين الأنواع المدروسة حيث سجل النوع( (E. geniculata أكبر حجم ( P = 46.21 mµ وE= 44.68 mµ ) للشكل الكروي ، و (P = 42.56 mµ , E= 37.54 mµ ) المتطاول ، بالمقابل سجل النوع ( pilulifera.E ) أصغر حجم وبلغ (P = 16 mµ , E = 15.62 mµ ) للشكل الكروي ، و (P = 17.68 mµ , E= 13.12mµ ) للمتطاول .This study indicated the presence of different shapes and sizes of grains starch in Milky liquid (latex) for 10 speciec of genus euphorbia these: , E.geniculata , E.pilulifera , E. serpens, E.prostrata , E. thamnoidesE. paralias , E. terracina , E. aleppica , E. peplus, ، E. helioscopiawhich varied between: (Rod) ,(Spindle), (Slightly osteoid), (Osteoid), (Dumb-blle), (Ostcoid branched), intermediate forms with indentation and accessories , pollen grains werw: spherical, or oval-shaped 3-colporate, It is of the Euphorbia hirta- type , and Ornamentation Tectum coarsely reticulate in (E.geniculata) only, and fine reticulate in the others species , and size of a Pollen grains differed between species .The largest size found in E. geniculata (P=46.21 mµ , E 44.68 = mµ)For spherical shape and (P = 42.56= m ,µ E 37.54= m µ)For elongated shape.The smallest size found in E.pilulifera (P=16mµ , E 15.62= mµ)For spherical shape and (P = 17.68 m ,µ E 13.12= m µ) For elongated shape.